Japan : Financial Sector Assessment Program-Technical Note on Credit Intermediation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper is an analysis of Japan's credit channel. The economic condition has no hindrance, but credit demand showed an inert performance. The state's policies have helped the flow of finance and prevent bankruptcy, but several other aspects act as an impediment to credit control. The Executive Board expects restructuring of financial policies in government-affiliated institutions, promotion of electronic registrations, risk-based financing, and reinforcing bank administrations. The Board takes up this paper as a study of Japan's thoughts in an efficient route to credit boom.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet